The influence of congenital heart disease on survival of infants with oesophageal atresia. Issue 3 (1st November 2001) - Leonard, H; Barrett, A M; Scott, J E S; Wren, C
Abstract : OBJECTIVE: To examine the prevalence of congenital heart disease in babies with oesophageal atresia and its influence on outcome. DESIGN: Retrospective analysis. SETTING: The resident population of one health region. RESULTS: A total of 153 babies with oesophageal atresia were identified from 509 975 live births (0.30 per 1000); 26 (17%) had cardiac defects. Survival of babies with normal hearts was 97%, 97%, and 95% at one week, one month, and one year. Survival of babies with congenital heart disease was 85%, 85%, and 67% at one week, one month, and one year, but only one of ten deaths was the result of the congenital heart disease. The remaining deaths were due to other congenital malformations, respiratory disease, or chromosome abnormalities. CONCLUSIONS: There is a high prevalence of congenital heart disease in babies with oesophageal atresia. Congenital heart disease is associated with a higher mortality in oesophageal atresia but it is not the cause of it.